Quality Indicators for the Diagnosis and Management of Sudden Sensorineural Hearing Loss. Issue 8 (26th September 2021) - Cottrell, Justin; Zahr, Siraj K.; Yip, Jonathan; Agrawal, Sumit; Archibald, Jason; Chau, Justin; Lea, Jane; Lin, Vincent; Mick, Paul; Morris, David; Parnes, Lorne; Schramm, David; et al.
Abstract : Objective: Sudden sensorineural hearing loss (SSNHL) is an ideal entity for quality indicator (QI) development, providing treatment challenges resulting in variable or substandard care. The American Academy of Otolaryngology—Head and Neck Surgery recently updated their SSNHL guidelines. With SSNHL demonstrating a large burden of illness, this study sought to leverage the updated guidelines and develop QIs that support quality improvement initiatives at an individual, institutional, and systems level. Methods: Candidate indicators (CIs) were extracted from high-quality SSNHL guidelines that were evaluated using the Appraisal of Guidelines for Research and Evaluation II tool. Each CI and its supporting evidence were summarized and reviewed by a nine-member expert panel based on validity, reliability, and feasibility of measurement. Final QIs were selected from CIs using the modified RAND Corporation-University of California, Los Angeles appropriateness methodology. Results: Fifteen CIs were identified after literature review. After the first round of evaluations, the panel agreed on 11 candidate indicators as appropriate QIs with 2 additional CIs suggested for consideration. An expert panel meeting provided a platform to discuss areas of disagreement before final evaluations. The expert panel subsequently agreed upon 11 final QIs as appropriate measures of high-quality care for SSNHL. Conclusion: The 11 proposed QIs from this study are supported by evidence and expert consensus, facilitating measurement across a wide breadth of quality domains. With the recently updated SSNHL guidelines, and a greater focus on quality improvement opportunities, these QIs may be used by healthcare providers for targeted quality improvement initiatives.